Polypropylene Composition for Automotive Interior Applications
A polypropylene-based composition combining recycled polyolefins with a heterophasic propylene copolymer and talc filler addresses the limitations of recycled materials in automotive interiors, enhancing mechanical and impact performance while reducing contamination and odor.
Patent Information
- Application Number
- JP2023575363
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-09
- Filing Date
- 2022-06-07
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2042-06-07
AI Technical Summary
The challenge in the automotive industry is the limited recyclability of polyolefins from household waste due to cross-contamination and the resulting inferior mechanical properties, odor, and emission issues in recycled polypropylene materials, which fail to meet the requirements for high flowability, mechanical strength, and surface appearance in automotive interior applications.
A polypropylene-based composition is developed by blending a mixed plastic polypropylene blend derived from post-consumer recycled polyolefin streams with a heterophasic propylene copolymer and an inorganic filler, such as talc, to achieve a balanced mechanical, thermal, and impact performance suitable for injection molding in automotive interiors.
The composition exhibits excellent mechanical properties, thermal stability, and improved impact resistance, particularly in instrumented impact tests, making it suitable for automotive interior applications with reduced tiger stripe defects and odor issues.
Smart Images

Figure 0007600439000001 
Figure 0007600439000002 
Figure 0007600439000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polypropylene composition comprising a mixed plastic polypropylene-based blend and an inorganic filler, particularly suitable for automotive interior applications. [Background technology]
[0002] Compositions suitable for the automotive industry typically contain one or more polypropylene heterophasic copolymers and / or random heterophasic copolymers, and conventionally some inorganic fillers. One of the fundamental challenges in the polymer business is recycling. At the moment, the market for recyclates, especially those from household waste, commonly called PCR ("post-consumer resins"), is somewhat limited. When starting from household waste, the sorting and separation processes employed do not make it possible to prepare pure polymers, i.e. there will always be some contaminants present, or the process may even result in a blend of different polymers. With regard to polyolefins, which constitute the majority of the polymer fraction of collected household waste, complete separation of polypropylene and polyethylene is hardly possible. Recycled polyolefin materials, especially post-consumer resins, are traditionally cross-contaminated with non-polyolefin materials such as polyethylene terephthalate, polyamide, polystyrene, or non-polymeric substances such as wood, paper, glass or aluminum. To make matters worse, these post-consumer recycled polyolefin materials, although readily available on a multi-ton scale, unfortunately have limited mechanical properties and often severe odor and / or emission problems. One major requirement in the automotive segment for interior applications is materials that have good flowability, high mechanical properties, respectively high stiffness-impact performance, and exhibit excellent surface appearance. In recent years, market demand has expanded towards using recycled polyolefins in blends with virgin polymers to meet specific requirements.
[0003] Unpublished patent application European Patent Application No. 20190814.2 relates to polypropylene compositions for automotive applications containing mixed plastic polypropylene-based blends derived from post-consumer recycled polyolefin streams and inorganic fillers, such as talc. These compositions exhibit beneficial VOC properties and tiger stripe performance (MSE), so that these compositions can replace sophisticated heterophasic polypropylene copolymers in automotive applications. However, these compositions still exhibit deficiencies in impact properties. Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention is based on the surprising finding that by carefully selecting the heterophasic propylene copolymer-based virgin component in a polypropylene-based composition containing a mixed plastic polypropylene-based blend derived from a post-consumer recycled polyolefin stream and an inorganic filler, such as talc, the polypropylene-based composition has an excellent balance of properties in terms of mechanical properties, thermal stability, and impact properties, especially in instrumented impact tests (puncture impact tests). Thus, the inventive composition comprising a mixed plastic polypropylene-based blend derived from a post-consumer recycled polyolefin stream is particularly suitable for injection molding applications in the automotive field, such as automotive interior applications, and can replace sophisticated heterophasic polypropylene copolymers. [Means for solving the problem]
[0005] The present invention relates to a composition suitable for automotive applications obtained by blending at least components (A), (B) and (C), (A) 15% to 50% by weight, preferably 17 to 47% by weight, more preferably 18 to 45% by weight, of a mixed plastic polypropylene blend; (B) 10% to 60% by weight, preferably 15 to 55% by weight, more preferably 17 to 52% by weight, of a heterophasic propylene copolymer, and (C) 5% by weight to 25% by weight, preferably 7% by weight to 22% by weight, more preferably 8% by weight to 20% by weight of an inorganic filler, All percentages are given relative to the total composition. The mixed plastic polypropylene blend (A) is a crystalline fraction (CF) content determined according to CRYSTEX QC analysis in the range of 85.0-96.0% by weight, preferably in the range of 86.5-95.5% by weight, and - soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of 4.0-15.0 wt.%, preferably in the range of 4.5-13.5 wt.%; having The crystalline portion (CF) is quantitatively in the range of 1.0 to 10.0% by weight, preferably in the range of 1.5 to 9.5% by weight. 13 having an ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; the soluble fraction (SF) has an intrinsic viscosity (iV(SF)) determined in decalin according to DIN ISO 1628 / 1 at 135° C. in the range of 0.9 to 2.1 dl / g, preferably in the range of 1.0 to 2.0 dl / g, more preferably in the range of 1.1 to 1.9 dl / g, The heterophasic propylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein, A melt flow rate MFR2 (230°C, 2.16 kg, ISO1133) of 85 to 250 g / 10 min, preferably 90 to 150 g / 10 min, more preferably 95 to 125 g / 10 min; A soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of >20.0% to 30.0% by weight, and an intrinsic viscosity (iV(SF)) of the soluble portion measured in decalin according to DIN ISO 1628 / 1 at 135° C. of 2.0 to 4.5 dl / g, preferably 2.4 to 3.8 dl / g, more preferably 2.5 to 3.7 dl / g; having The composition comprises: Melt flow rate MFR2 (230°C, 2.16 kg, ISO1133) of 20 to 60 g / 10 min, preferably 21 to 50 g / 10 min, more preferably 22 to 45 g / 10 min The present invention relates to a composition having the formula:
[0006] Furthermore, the present invention relates to an article, preferably a molded article, more preferably an automotive molded article, comprising the composition as described above or below. Still further, the present invention relates to the use of the above or below described composition for injection molding of an article, preferably an automotive article, more preferably an automotive interior article.
[0007] definition Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Although any methods and materials similar or equivalent to those described herein can be used in the practice of testing the present invention, the preferred materials and methods are described herein. In describing and claiming the present invention, the following terms are used in accordance with the definitions set forth below. Unless expressly stated otherwise, the use of terms such as "a" and "an" refers to one or more.
[0008] Mixed plastics are defined as the presence of small amounts of compounds not normally found in virgin (virgin) polypropylene blends, such as polystyrene, polyamides, polyesters, wood, paper, limonene, aldehydes, ketones, fatty acids, metals, and / or long-term degradation products of stabilizers. Virgin polypropylene blends refer to blends that originate directly from the manufacturing process without intermediate uses. As a matter of definition, a "mixed plastic" may contain detectable amounts of polystyrene and / or polyamide-6 and / or limonene and / or fatty acids. Thus, mixed plastics, in contrast to virgin polymers, may originate from both post-consumer and post-industrial sources. Post-consumer waste refers to objects that have completed at least a first use cycle (or life cycle), i.e. have already fulfilled their first purpose. In contrast, post-industrial waste refers to manufacturing scrap, or conversion scrap, which usually does not reach the consumer.
[0009] Those skilled in the art will appreciate that the soluble fraction (SF) obtained by CRYSTEX QC analysis having an intrinsic viscosity (iV(SF)) in the range of 0.9 to less than 2.2 dl / g is typically found in materials from recycle streams. In a preferred embodiment of the invention, the soluble fraction (SF) obtained by CRYSTEX QC analysis has an intrinsic viscosity (iV(SF)) in the range of 0.9 to 2.1 dl / g.
[0010] A polymer blend is a mixture of two or more polymer components. Generally, the blend can be prepared by mixing two or more polymer components. A suitable mixing procedure known in the art is post-polymerization blending. The post-polymerization blend can be a dry blend of the polymer components, such as polymer powder and / or polymer pellets via compounding, or a melt blend by melt mixing the polymer components.
[0011] "Polypropylene-polyethylene blend" refers to a composition containing both polypropylene and polyethylene, including polypropylene and polyethylene copolymers. Direct determination of polypropylene and polyethylene content is not possible, and the weight ratios of polypropylene (A-1) to polyethylene (A-2) of 19:1 to 7:3 represent equivalence ratios determined from calibration with iPP and HDPE and determination by IR spectroscopy.
[0012] Polypropylene means a polymer composed of greater than 50 mole % units derived from propylene. By polyethylene is meant a polymer composed of greater than 50 mole % units derived from ethylene.
[0013] The term "elastomer" refers to a natural or synthetic polymer having elastic properties. The term "plastomer" refers to a natural or synthetic polymer that combines the properties of elastomers and plastics, e.g., rubber-like properties with the processability of plastics. Ethylene-based plastomer means a plastomer composed of more than 50 mole % units derived from ethylene.
[0014] The presence of heterophasicity can be readily determined, for example, by the number of glass transitions in dynamic mechanical analysis (DMA) and / or by high-resolution microscopy such as scanning electron microscopy (SEM), transmission electron microscopy (TEM) or atomic force microscopy (AFM).
[0015] The term "XCS" refers to the cold xylene solubles (fraction) (XCS wt%) determined according to ISO 16152 at 25° C. The term "XCI" refers to the cold xylene insolubles (fraction) (XCI wt%) determined according to ISO 16152 at 25° C.
[0016] A reactor blend is a blend resulting from production in two or more reactors connected in series, or in a reactor having two or more reaction zones. Alternatively, a reactor blend may result from blending in solution. Reactor blends are in contrast to formulations such as those produced by melt extrusion.
[0017] Unless otherwise indicated, "%" refers to % by weight. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] composition In a first aspect, the present invention relates to a composition suitable for automotive applications obtained by blending at least components (A), (B) and (C), (A) 15% to 50% by weight, preferably 17 to 47% by weight, more preferably 18 to 45% by weight, of a mixed plastic polypropylene blend; (B) 10% to 60% by weight, preferably 15 to 55% by weight, more preferably 17 to 52% by weight, of a heterophasic propylene copolymer, and (C) 5% by weight to 25% by weight, preferably 7% by weight to 22% by weight, more preferably 8% by weight to 20% by weight of an inorganic filler, All percentages are given relative to the total composition. The mixed plastic polypropylene blend (A) is a crystalline fraction (CF) content, determined according to CRYSTEX QC analysis, in the range of 85.0 to 96.0% by weight, preferably in the range of 86.5 to 95.5% by weight, and - soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of 4.0-15.0 wt.%, preferably in the range of 4.5-13.5 wt.% having The crystalline portion (CF) is quantitatively in the range of 1.0 to 10.0% by weight, preferably in the range of 1.5 to 9.5% by weight. 13 having an ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; the soluble fraction (SF) has an intrinsic viscosity (iV(SF)) measured in decalin according to DIN ISO 1628 / 1 at 135° C. in the range of 0.9 to 2.1 dl / g, preferably in the range of 1.0 to 2.0 dl / g, more preferably in the range of 1.1 to 1.9 dl / g, The heterophasic propylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein, A melt flow rate MFR2 (230°C, 2.16 kg, ISO1133) of 85 to 250 g / 10 min, preferably 90 to 150 g / 10 min, more preferably 95 to 125 g / 10 min; A soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of >20.0% to 30.0% by weight, and an intrinsic viscosity (iV(SF)) of the soluble portion measured in decalin according to DIN ISO 1628 / 1 at 135° C. of 2.0 to 4.5 dl / g, preferably 2.4 to 3.8 dl / g, more preferably 2.5 to 3.7 dl / g; having The composition comprises: Melt flow rate MFR2 (230°C, 2.16 kg, ISO1133) of 20 to 60 g / 10 min, preferably 21 to 50 g / 10 min, more preferably 22 to 45 g / 10 min The present invention relates to a composition having the formula:
[0019] The automotive compositions of the present invention are particularly suited for injection molding of articles for use in the interior of a vehicle. Compositions suitable for automotive applications according to the present invention have one or more of the following characteristics:
[0020] The composition has a melt flow rate MFR2 (230° C., 2.16 kg, ISO 1133) of 20 to 60 g / 10 min, preferably 21 to 50 g / 10 min, more preferably 22 to 45 g / 10 min.
[0021] The composition can be characterized by CRYSTEX QC analysis, which provides the crystalline fraction (CF) and soluble fraction (SF), which can be quantified and analyzed for monomer and comonomer content and intrinsic viscosity (iV). The composition preferably exhibits one or all of the following characteristics in a CRYSTEX QC analysis: a crystalline fraction (CF) content, determined according to CRYSTEX QC analysis, in the range of 60.0-90.0 wt.%, preferably 65.0-88.0 wt.%, and · Soluble fraction (SF) content, determined according to CRYSTEX QC analysis, in the range of 10.0-40.0 wt.%, preferably 12.0-35.0 wt.%.
[0022] The crystalline portion (CF) preferably has one or more, preferably all, of the following properties: Quantitatively in the range of 4.0 to 15.0% by weight, preferably 4.5 to 14.5% by weight 13 ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy, and / or An intrinsic viscosity (iV(CF)), measured in decalin according to DIN ISO 1628 / 1 at 135° C., of less than 1.8 dl / g, preferably between 0.8 and 1.7 dl / g.
[0023] The fusible part (SF) preferably has one or more, preferably all, of the following properties: Quantitatively in the range of 28.0 to 65.0% by weight, preferably 30.0 to 60.0% by weight 13 ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy, and / or An intrinsic viscosity (iV(SF)), measured in decalin according to DIN ISO 1628 / 1 at 135° C., of more than 1.7 dl / g, preferably between 1.8 and 2.6 dl / g.
[0024] The composition preferably comprises units derived from ethylene in an amount of from 10.0 to 30.0% by weight, more preferably from 12.5 to 27.5% by weight, even more preferably from 15.0 to 25.0% by weight.
[0025] The compositions according to the present invention preferably exhibit an excellent balance of properties with respect to mechanical properties, thermal stability, and impact properties, especially in, for example, instrumented impact tests.
[0026] The composition preferably has a flexural modulus of 1500 MPa to 2200 MPa, more preferably 1600 MPa to 2000 MPa.
[0027] Furthermore, the composition preferably has a thermal conductivity of 5.0 kJ / m 2 , ~50.0kJ / m 2 , more preferably 5.5 to 45.0 kJ / m 2 It has a notched Charpy impact strength (CNIS at 23°C) of 1.0 to 1.5 mm at 23°C.
[0028] Even more preferably, the composition has very good impact strength in an instrumented impact test, especially at low temperatures. The composition preferably has a puncture energy measured at 23°C of 12-65J, more preferably 14-60J. The composition preferably has an energy at maximum force measured at 23°C of 10 to 60 J, more preferably 12 to 55 J. Furthermore, the composition preferably has a puncture energy measured at 0°C of 3 to 50 J, more preferably 5 to 45 J. The composition preferably has a maximum impact energy measured at 0°C of 3 to 50 J, more preferably 5 to 45 J. Still further, the composition preferably has a puncture energy measured at -30°C of 3 to 50 J, more preferably 5 to 45 J. The composition preferably has a maximum impact energy of 3 to 50 J, more preferably 5 to 45 J, measured at -30°C.
[0029] In addition, the composition preferably has a deflection temperature under load (ISO75B) of at least 95°C, more preferably from 96°C to 110°C.
[0030] Furthermore, the composition preferably has a coefficient of linear thermal expansion (CLTE) of 60 to 125 μm / mK, more preferably 70 to 105 μm / mK.
[0031] The composition of the present invention essentially comprises components (A), (B) and (C) described above or below in the amounts correspondingly described.
[0032] The composition may optionally comprise an additional polymer component, so that the composition may be obtained by blending components (A), (B), (C) and one or more of the following components: (D) 0-25 wt.-%, preferably 0-23 wt.-%, more preferably 0-20 wt.-% of a second heterophasic propylene copolymer, (E) 0 to 10% by weight, preferably 0 to 9% by weight, more preferably 0 to 8% by weight, of high-density polyethylene, (F) 0 to 20% by weight, preferably 0 to 18% by weight, more preferably 0 to 16% by weight, of an ethylene-based plastomer; All percentages are given relative to the total composition. The second heterophasic propylene copolymer (D) comprises a matrix phase and an elastomeric phase dispersed therein; A melt flow rate MFR2 (230°C, 2.16 kg, ISO1133) of 8 to 25 g / 10 min, preferably 10 to 24 g / 10 min, more preferably 12 to 23 g / 10 min; a soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of 12.5 to 30.0% by weight, preferably in the range of 14.0 to 27.0% by weight, more preferably in the range of 15.0 to 25.0% by weight, and the intrinsic viscosity iV(SF) of the soluble portion measured in decalin according to DIN ISO 1628 / 1 at 135° C. in the range of 2.3 dl / g to 6.0 dl / g, preferably 2.5 to 5.5 dl / g, more preferably 2.6 to 4.5 dl / g; having High density polyethylene (E) is ·Melt flow rate MFR2 (190℃, 2.16kg, ISO1133) of 0.5 to 30.0g / 10min, and 945~965kg / m 3 Density of having The ethylene-based plastomer, which is a copolymer of ethylene and a comonomer unit selected from an α-olefin having 3 to 12 carbon atoms, preferably an α-olefin having 4 to 10 carbon atoms, and most preferably 1-octene, A melt flow rate MFR2 (190°C, 2.16 kg, ISO1133) of 0.2 to 2.5 g / 10 min, preferably 0.3 to 2.0 g / 10 min, and 850~870kg / m 3, preferably 855 to 865 kg / m 3 Density of has.
[0033] In one embodiment, the composition is obtained by blending components (A), (B), (C) and (F), in the absence of (D) and (E); (A) 15% to 35% by weight, preferably 17 to 32% by weight, more preferably 18 to 30% by weight of a mixed plastic polypropylene blend, (B) 30% to 60% by weight, preferably 35 to 55% by weight, more preferably 40 to 52% by weight of a first heterophasic propylene copolymer, (C) 5% by weight to 25% by weight, preferably 7% by weight to 22% by weight, more preferably 8% by weight to 20% by weight of an inorganic filler, and (F) 5% to 20% by weight, preferably 7 to 18% by weight, more preferably 8 to 16% by weight, of an ethylene-based plastomer; All percentages are given relative to the total composition.
[0034] In another embodiment, the composition is obtained by blending components (A), (B), (C), (E) and (F), in the absence of (D); (A) 25% to 50% by weight, preferably 27 to 47% by weight, more preferably 30 to 45% by weight, of a mixed plastic polypropylene blend, (B) 20% to 50% by weight, preferably 25 to 45% by weight, more preferably 30 to 42% by weight of a first heterophasic propylene copolymer, (C) 5% by weight to 25% by weight, preferably 7% by weight to 22% by weight, more preferably 8% by weight to 20% by weight of an inorganic filler, (E) 2 to 10% by weight, preferably 3 to 9% by weight, more preferably 5 to 8% by weight, of high-density polyethylene, and (F) 2% to 20% by weight, preferably 3% to 18% by weight, more preferably 4% to 16% by weight, of an ethylene-based plastomer; All percentages are given relative to the total composition.
[0035] In yet another embodiment, the composition is obtained by blending components (A), (B), (C), (D) and (E), in the absence of (F); (A) 25% to 50% by weight, preferably 27 to 47% by weight, more preferably 30 to 45% by weight, of a mixed plastic polypropylene blend, (B) 15% to 30% by weight, preferably 17 to 27% by weight, more preferably 18 to 25% by weight of a first heterophasic propylene copolymer, (C) 5% by weight to 25% by weight, preferably 7% by weight to 22% by weight, more preferably 8% by weight to 20% by weight of an inorganic filler, (D) 5% to 25% by weight, preferably 8 to 23% by weight, more preferably 10 to 20% by weight of a second heterophasic propylene copolymer, and (E) 2 to 10% by weight, preferably 3 to 9% by weight, more preferably 5 to 8% by weight, of high-density polyethylene, All percentages are given relative to the total composition.
[0036] Mixed Plastic Polypropylene Blend (A) The mixed plastic polypropylene blend (A) is suitably characterized by CRYSTEX QC analysis, which provides the crystalline fraction (CF) and soluble fraction (SF), which can be quantified and analyzed for monomer and comonomer content and intrinsic viscosity (iV). The mixed plastic polypropylene blend (A) exhibits the following characteristics in the CRYSTEX QC analysis: a crystalline fraction (CF) content, determined according to CRYSTEX QC analysis, in the range of 85.0 to 96.0% by weight, preferably in the range of 86.5 to 95.5% by weight, more preferably in the range of 88.0 to 95.0% by weight, and · A soluble fraction (SF) content, determined according to CRYSTEX QC analysis, in the range of 4.0-15.0 wt.%, preferably in the range of 4.5-13.5 wt.%, more preferably in the range of 5.0-12.0 wt.%.
[0037] The crystalline portion (CF) has one or more, preferably all, of the following properties: Quantitatively in the range of 1.0 to 10.0% by weight, preferably in the range of 1.5 to 9.5% by weight, more preferably in the range of 2.0 to 9.0% by weight 13 ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy, and / or An intrinsic viscosity (iV(CF)), measured in decalin according to DIN ISO 1628 / 1 at 135° C., preferably in the range of 1.0 to 2.6 dl / g, more preferably in the range of 1.2 to 2.5 dl / g, even more preferably in the range of 1.3 to 2.4 dl / g.
[0038] The fusible portion (SF) has one or more, preferably all, of the following properties: Quantitatively, preferably in the range of 20.0 to 55.0% by weight, preferably in the range of 22.0 to 50.0% by weight, more preferably in the range of 24.0 to 48.0% by weight 13 ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy, and / or An intrinsic viscosity (iV(SF)), measured in decalin according to DIN ISO 1628 / 1 at 135° C., in the range of 0.9 to 2.1 dl / g, preferably in the range of 1.0 to 2.0 dl / g, more preferably in the range of 1.1 to 1.9 dl / g.
[0039] Preferably, the mixed plastic polypropylene blend (A) comprises polypropylene and polyethylene. The weight ratio of polypropylene to polyethylene is preferably 19:1 to 7:3.
[0040] The mixed plastic polypropylene blend (A) preferably contains more than 50 mole % of units derived from propylene.
[0041] The mixed plastic polypropylene blend (A) preferably comprises units derived from ethylene in an amount of 2.5 to 15.0% by weight, more preferably 4.0 to 12.5% by weight, even more preferably 5.0 to 10.0% by weight.
[0042] Furthermore, the mixed plastic polypropylene blend (A) preferably has one or more, preferably all, of the following properties: A melt flow rate MFR2 (230°C, 2.16 kg, ISO1133) of 8.0 to 40 g / 10 min, preferably 9.0 to 35 g / 10 min, more preferably 10.0 to 30 g / 10 min, and / or Limonene content determined by using solid phase microextraction (HS-SPME-GC-MS): 0.1 ppm to 50 ppm, and / or a tensile modulus of 1000 MPa to 1500 MPa, preferably 1100 MPa to 1400 MPa, and / or 3.0~7.5kJ / m 2 , preferably 4.0 to 7.0 kJ / m 2 Charpy notched impact strength at 23°C (CNIS at 23°C).
[0043] The mixed plastic polypropylene blend according to the present invention is preferably in the form of pellets, which contributes to a low amount of volatile materials.
[0044] Heterophasic propylene copolymer (B) The heterophasic polypropylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein.
[0045] The heterophasic propylene copolymer (B) is A melt flow rate MFR2 (230°C, 2.16 kg, ISO1133) of 85 to 250 g / 10 min, preferably 90 to 150 g / 10 min, more preferably 95 to 125 g / 10 min; a soluble fraction (SF) content, determined according to CRYSTEX QC analysis, in the range of 20.0-30.0 wt.%, preferably 20.5-28.0 wt.%, more preferably 21.0-26.0 wt.%, and an intrinsic viscosity iV(SF) of the soluble portion measured in decalin according to DIN ISO 1628 / 1 at 135° C. of 2.0 dl / g to 4.5 dl / g, preferably 2.4 to 3.8 dl / g, more preferably 2.5 to 3.7 dl / g; It is characterized by:
[0046] Preferably, the heterophasic propylene copolymer (B) has one or more, preferably all, of the following properties: a content (C2) of units derived from ethylene in the soluble fraction (SF) of 30 to 45% by weight, preferably 32 to 40% by weight, more preferably 33 to 38% by weight, and / or a content (C2) of units derived from ethylene in the crystalline portion (CF) of 0.1 to 5.0% by weight, preferably 0.2 to 4.0% by weight, more preferably 0.5 to 3.0% by weight, and / or a total content of units derived from ethylene (C2) of 5.0 to 15.0% by weight, preferably 6.0 to 12.0% by weight, more preferably 7.0 to 10.0% by weight, and / or an intrinsic viscosity iV(CF) of the crystalline part determined according to CRYSTEX QC analysis and measured in decalin according to DIN ISO 1628 / 1 at 135°C of 0.8 to 2.0 dl / g, preferably 0.9 to 1.8 dl / g, and / or a melting temperature Tm of 155 to 175°C, preferably 157 to 172°C, more preferably 160 to 170°C, and / or a crystallization temperature Tc of 120 to 140° C., preferably 122 to 137° C., more preferably 125 to 135° C., and / or a tensile modulus of 1250 MPa to 1800 MPa, preferably 1300 MPa to 1750 MPa, more preferably 1350 MPa to 1700 MPa, and / or 4.0~8.5kJ / m 2 , preferably 5.0 to 7.0 kJ / m 2Notched Charpy impact strength at 23°C (CNIS at 23°C). The heterophasic propylene copolymer (B) preferably consists of propylene and ethylene units. Although not measured, the content (C3) of units derived from propylene in the soluble fraction (SF) preferably amounts to 100% by weight when combined with the content (C2) of units derived from ethylene in the soluble fraction (SF). The content (C3) of units derived from propylene in the soluble fraction (SF) is preferably 55 to 70% by weight, more preferably 60 to 68% by weight, and even more preferably 62 to 67% by weight. Although not measured, the content (C3) of units derived from propylene in the crystalline portion (CF) preferably becomes 100% by weight when combined with the content (C2) of units derived from ethylene in the crystalline portion (CF). The content (C3) of units derived from propylene in the crystalline portion (CF) is preferably 95.0 to 99.9% by weight, more preferably 96.0 to 99.8% by weight, and even more preferably 97.0 to 99.5% by weight. The total content (C3) of units derived from propylene in the heterophasic propylene copolymer (B) is preferably from 85.0 to 95.0 wt.-%, more preferably from 88.0 to 94.0 wt.-%, even more preferably from 90.0 to 93.0 wt.-%.
[0047] Such heterophasic propylene copolymers are commercially available.
[0048] Inorganic filler (C) As the inorganic filler (C), talc is preferred.
[0049] The inorganic filler, preferably talc, (C) preferably has a median particle size (median particle size) d before compounding of 0.3 to 30.0 micrometers, more preferably 1.5 to 15.0 micrometers. 50 has.
[0050] Furthermore, the inorganic filler, preferably talc, (C) preferably has a top-cut particle size d before compounding of 1.0 to 50.0 micrometers, preferably 5.0 to 35.0 micrometers. 95 has.
[0051] Such inorganic fillers are commercially available.
[0052] Additives Additives are commonly used in the compositions according to the invention. Preferably, the additives are selected from one or more of antioxidants, UV stabilizers, slip agents, nucleating agents, pigments, lubricants, masterbatch polymers (each of which may be plural) and / or anti-fog agents. The additives are usually present in the composition in an amount of 0.01 to 4.0% by weight, and preferably 0.05 to 3.0% by weight, based on the total weight of the composition.
[0053] Second heterophasic propylene copolymer (D) The optional heterophasic polypropylene copolymer (D) comprises a matrix phase and an elastomeric phase dispersed therein.
[0054] The second heterophasic propylene copolymer (D), if present in the composition, preferably has a melt flow rate lower than the melt flow rate of the heterophasic propylene copolymer (B). The optional second heterophasic propylene copolymer (D) has a melt flow rate MFR2 (230° C., 2.16 kg, ISO 1133) of 8 to 25 g / 10 min, preferably 10 to 24 g / 10 min, more preferably 12 to 23 g / 10 min.
[0055] Further, the optional second heterophasic propylene copolymer (D) has a solubles (SF) content, determined according to CRYSTEX QC analysis, in the range of 12.5-30.0 wt.%, preferably in the range of 14.0-27.0 wt.%, more preferably in the range of 15.0-25.0 wt.%. The soluble portion preferably has an intrinsic viscosity iV(SF), measured in decalin according to DIN ISO 1628 / 1 at 135° C., of 2.3 dl / g to 6.0 dl / g, preferably 2.5 to 5.5 dl / g, more preferably 2.6 to 4.5 dl / g.
[0056] The optional second heterophasic propylene copolymer (D) preferably has a crystalline fraction (CF) content, determined according to CRYSTEX QC analysis, in the range of 70.0 to 87.5 wt.%, preferably in the range of 73.0 to 86.0 wt.%, more preferably in the range of 75.0 to 85.0 wt.%.
[0057] Preferably, the optional second heterophasic propylene copolymer (D) has one or more, preferably all, of the following properties: a content of units derived from ethylene in the soluble fraction (SF) of 30 to 45% by weight, preferably 32 to 40% by weight, more preferably 33 to 38% by weight, and / or a content of units derived from ethylene in the crystalline fraction (CF) of 0.5 to 7.5% by weight, preferably 1.0 to 5.0% by weight, more preferably 1.5 to 4.0% by weight, and / or a total content of units derived from ethylene of 5.0 to 15.0% by weight, preferably 6.0 to 12.0% by weight, more preferably 6.5 to 10.0% by weight, and / or an intrinsic viscosity iV(CF) of the crystalline part determined according to CRYSTEX QC analysis and measured in decalin according to DIN ISO 1628 / 1 at 135° C. in the range of 1.0 to 2.0 dl / g, preferably in the range of 1.1 to 1.9 dl / g, and / or a melting temperature Tm of 155 to 175°C, preferably 157 to 172°C, more preferably 160 to 170°C, and / or A crystallization temperature Tc of 120 to 140°C, preferably 122 to 137°C, more preferably 125 to 135°C.
[0058] The optional heterophasic propylene copolymer (D) preferably consists of propylene and ethylene units. Although not measured, the content (C3) of units derived from propylene in the soluble fraction (SF) preferably amounts to 100% by weight when combined with the content (C2) of units derived from ethylene in the soluble fraction (SF). The content (C3) of units derived from propylene in the soluble fraction (SF) is preferably 55 to 70% by weight, more preferably 60 to 68% by weight, and even more preferably 62 to 67% by weight. Although not measured, the content (C3) of units derived from propylene in the crystalline portion (CF) preferably becomes 100% by weight when combined with the content (C2) of units derived from ethylene in the crystalline portion (CF). The content (C3) of units derived from propylene in the crystalline portion (CF) is preferably 92.5 to 99.5% by weight, more preferably 95.0 to 99.0% by weight, and even more preferably 96.0 to 98.5% by weight. The total content (C3) of units derived from propylene in the heterophasic propylene copolymer (B) is preferably from 85.0 to 95.0 wt.-%, more preferably from 88.0 to 94.0 wt.-%, even more preferably from 90.0 to 93.5 wt.-%.
[0059] The optional second heterophasic polypropylene copolymer (D) is preferably nucleated, more preferably nucleated by poly(vinylcyclohexane), as described, for example, in EP 2 960 279 B1.
[0060] Such heterophasic propylene copolymers are commercially available.
[0061] High density polyethylene (E) High density polyethylene (E), in particular virgin high density polyethylene (E), may be added to the composition according to the invention. The high density polyethylene (E) contributes to the scratch resistance of the final composition. Due to the presence of high density polyethylene in the blend (A), the amount of high density polyethylene (E) for the targeted scratch resistance may be reduced or omitted completely.
[0062] The optional high density polyethylene (E) preferably has one or more, preferably all, of the following characteristics: Melt flow rate MFR2 (190℃, 2.16kg, ISO1133) of 0.5 to 30.0g / 10min, and / or 945~965kg / m 3 Density.
[0063] Such high density polyethylene is commercially available.
[0064] Ethylene-based plastomer (F) The optional ethylenic plastomer (F) is preferably a copolymer of ethylene and comonomer units selected from an α-olefin having from 3 to 12 carbon atoms, preferably an α-olefin having from 4 to 10 carbon atoms, and most preferably 1-octene. Ethylene-based plastomers are typically added to further improve the impact properties of the composition.
[0065] The optional ethylenic plastomer (F) preferably has one or more, preferably all, of the following properties: A melt flow rate MFR2 (190°C, 2.16 kg, ISO1133) of 0.2 to 2.5 g / 10 min, preferably 0.3 to 2.0 g / 10 min, and 850~870kg / m 3 , preferably 855 to 865 kg / m 3 Density.
[0066] Such ethylenic plastomers are commercially available under trade names such as Engage, Exact, Queo, and Tafmer.
[0067] Goods In another aspect, the present invention relates to an article, preferably a molded article, more preferably an automotive molded article, comprising the above or below described composition. The article is preferably for use inside a vehicle.
[0068] The article preferably exhibits good surface quality. The article preferably has an MSE surface quality of less than 15, preferably less than 14.
[0069] use In yet another aspect, the present invention relates to the use of the above or below described composition for injection molding of an article, preferably an automotive article, more preferably an automotive interior article. EXAMPLES
[0070] Experimental section The following examples are included to demonstrate certain aspects and embodiments of the claimed invention. However, it should be understood by those of ordinary skill in the art that the following descriptions are illustrative only and should not be construed as limiting the invention in any way.
[0071] Test Method a) CRYSTEX Determination of the crystalline and soluble fractions and their respective properties (IV and ethylene content) The crystalline (CF) and soluble (SF) fractions of the polypropylene compositions, as well as the comonomer content and intrinsic viscosity of each fraction, were analyzed by using a CRYSTEX instrument, Polymer Char (Valencia, Spain). Details of the technique and method can be found in the literature (Ljiljana Jeremic, Andreas Albrecht, Martina Sandholzer, and Markus Gahleitner (2020) Rapid characterization of high-impact ethylene-propylene copolymer composition by crystallization extraction separation: comparability to standard separation methods, International Journal of Polymer Analysis and Characterization, 25:8, 581-596). The crystalline and amorphous parts are separated by a temperature cycle of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. Quantification of SF and CF and determination of the ethylene content (C2) are achieved by an integrated infrared detector (IR4) and for the determination of the intrinsic viscosity (iV) an online two-capillary viscometer is used. The IR4 detector detects two different bands: the CH stretching vibration (approximately 2960 cm), which helps determine the concentration and ethylene content in ethylene-propylene copolymers. -1 ) and CH stretching vibration (2700-3000cm -1 )) is a multi-wavelength detector that measures IR absorbance at 100 nm and 100 nm wavelengths. The IR4 detector measures ethylene content ( 13 A series of eight EP copolymers with different ethylene content (determined by C-NMR) are used to calibrate, each at different concentrations ranging from 2 to 13 mg / ml. To simultaneously address both characteristics, concentration and ethylene content, for the different polymer concentrations (Conc) expected during the Crystex analysis, the following calibration equation was applied:
[0072] Conc=a+b×Abs(CH)+c×(Abs(CH)) 2 +d×Abs(CH3)+e×(Abs(CH3) 2 +f×Abs(CH)×Abs(CH3) (Formula 1) CH3 / 1000C=a+b×Abs(CH)+c×Abs(CH3)+d×(Abs(CH3) / Abs(CH))+e×(Abs(CH3) / Abs(CH)) 2 (Formula 2)
[0073] Constants a to e in Equation 1 and constants a to f in Equation 2 were determined using least squares regression analysis. CH3 / 1000C is converted to ethylene content (wt%) using the following relationship: Weight % (ethylene in EP copolymer) = 100-CH3 / 1000TC x 0.3 (Equation 3) The amount of soluble (SF) and crystalline (CF) fractions are correlated with the amount of "cold xylene soluble" (XCS) and the cold xylene insoluble (XCI) fraction, respectively, by XS calibration, determined according to standard gravimetric methods according to ISO 16152. The XS calibration is achieved by testing various EP copolymers with XS contents ranging from 2 to 31 wt.%. The determined XS calibration is linear. Weight%XS=1.01×Weight%SF (Formula 4) The intrinsic viscosities (iV) of the parent EP copolymer as well as its soluble and crystalline parts are determined using an on-line two-capillary viscometer and correlated with the corresponding iV determined by standard methods in decalin according to ISO 1628-3. Calibration is achieved using various EPPP copolymers with iV = 2-4 dL / g. The determined calibration curve is linear. iV(dL / g)=a×Vsp / c (Formula 5)
[0074] The samples to be analyzed are weighed out at a concentration of 10 mg / ml to 20 mg / ml. The weighed samples are packed into a stainless steel mesh MW 0.077 / D 0.05 mmm to avoid the injection of possible gels and / or polymers that are not soluble in TCB at 160°C, such as PET and PA. After autofilling the vials with 1,2,4-TCB containing 250 mg / l 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the samples are dissolved at 160° C. with constant stirring at 400 rpm until complete dissolution is achieved, typically for 60 min. The polymer solution is covered with a N2 atmosphere during dissolution to avoid sample degradation. A defined volume of the sample solution is injected into a column packed with an inert carrier where the crystallization of the sample and the separation of the soluble part from the crystalline part take place. This process is repeated twice. During the first injection, the entire sample is measured at high temperature and the iV [dl / g] and C2 [wt%] of the PP composition are determined. During the second injection, the soluble part (at low temperature) and the crystalline part (at high temperature) are measured in the crystallization cycle (wt% SF, wt% C2, iV).
[0075] b) Cold xylene solubles (XCS, wt%) The xylene cold soluble (XCS) fraction was determined according to ISO 16152; 1st edition; 2005-07-01 at 25° C. The part that remains insoluble is the xylene cold insoluble (XCI) fraction.
[0076] c) Intrinsic viscosity The intrinsic viscosity was determined according to DIN ISO 1628 / 1, October 1999 (135° C. in decalin).
[0077] d) Charpy notched impact strength 80x10x4mm prepared according to EN ISO1873-2 3 The thermal expansion coefficient was determined according to ISO 179-1eA on injection molded specimens at +23° C. and −20° C. Measurements were performed after a conditioning time of 96 hours at 23° C.
[0078] e) Flexural modulus Flexural modulus is measured on 80x10x4mm specimens prepared by injection molding according to EN ISO1873-2 3 The strength was determined according to ISO 178 for a test specimen having dimensions of (length x width x thickness), with a support distance of 64 mm, a test speed of 2 mm / min, and a force of 100 N.
[0079] f) Tensile modulus Measurements were performed according to ISO 527-2 (crosshead speed = 1 mm / min; test speed 50 mm / min, 23°C) using injection moulded specimens 1B (dogbone shape, 4 mm thick) prepared as described in EN ISO 1873-2. Measurements were performed after a conditioning time of the specimens of 96 hours at 23°C.
[0080] g) Instrumented impact test (puncture impact test) The instrumented impact test is 60 x 60 x 3 mm 3 Tests were performed according to ISO 6603-2:2000 on injection molded plaques at 23° C., 0° C. and −30° C. Measurements were performed after a conditioning period of 96 hours at 23° C. on the test specimens.
[0081] h) Comonomer Content Poly(propylene-co-ethylene) - Ethylene Content - IR Spectroscopy Quantitative infrared (IR) spectroscopy was used to quantify the ethylene content of poly(ethylene-co-propene) copolymers by calibration to the primary method. 13 The calibration was facilitated by the use of a set of in-house, non-commercially available calibration standards of known ethylene content determined by C solution-state nuclear magnetic resonance (NMR) spectroscopy. The calibration procedure was performed by conventional methods well described in the literature. The calibration set consisted of 38 calibration standards with ethylene contents ranging from 0.2 to 75.0 wt% that were produced at either pilot or full scale under a variety of conditions. The calibration set was selected to reflect the typical diversity of copolymers encountered in the eventual quantitative IR spectroscopy. Quantitative IR spectra were recorded in the solid state using a Bruker Vertex 70 FTIR spectrometer. Spectra were recorded on 25 × 25 mm square films with a thickness of 300 μm prepared by compression molding at 180-210 °C and 4-6 MPa. For samples with very high ethylene content (>50 mol%), 100 μm thick films were used. Standard transmission FTIR spectroscopy was employed, ranging from 5000 to 500 cm. -1 Spectral range, 6mm aperture, 2cm -1 A spectral resolution of 16, 16 background scans, 16 spectral scans, an interferogram zero-filling factor of 64, and Blackmann-Harris 3-term apodization were used. (CH2) >2 730 and 720 cm corresponding to the structural units -1 The total area of the CH2 antisymmetric in-plane bending (rolling) in Q ) (integration method G, limits 762 and 694 cm -1 Quantitative analysis was performed using the CH structural unit (integration method G, limits 4650, 4007 cm). -1 ) corresponds to 4323cm -1 The area of the CH band (A RThe ethylene content in weight percent was then normalized to the normalized absorbance (A) using a quadratic calibration curve. Q / A R ) The calibration curve was previously constructed by ordinary least squares (OLS) regression of the normalized absorbance and primary comonomer content measured on the calibration set.
[0082] Poly(propylene-co-ethylene) - Ethylene content - 13 C NMR spectroscopy quantitative 13 C{ 1 The H}NMR spectrum 1 H and 13 All spectra were recorded in solution using a Bruker Avance III 400 NMR spectrometer operating at 400.15 and 100.62 MHz for C, respectively. 13 All air pressures were recorded using nitrogen gas using a 10 mm extended temperature probe head optimized for C. Approximately 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) with chromium(III) acetylacetonate (Cr(acac)3) giving a 65 mM solution of the relaxation agent in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, after the initial sample preparation in a heat block, the NMR tube was further heated in a rotating oven for at least 1 h. After insertion into the magnet, the tube was spun at 10 Hz. This setting was chosen mainly due to the high resolution and quantitation required for accurate ethylene content quantification. Standard single pulse excitation without NOE was employed, using an optimized tip angle, a recycle delay of 1 s, and a bilevel WALTZ16 decoupling scheme (Zhou, Z. et al., J. Mag. Reson. 187 (2007) 225 and Busico, V. et al., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were acquired per spectrum. Quantitative 13 C{ 1 H} NMR spectra were processed, integrated, and relevant quantitative properties were determined from the integrals. All chemical shifts were indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This approach allowed for comparable referencing in the absence of this structural unit. Characteristic signals corresponding to ethylene incorporation were observed (Cheng, HN, Macromolecules 17 (1984), 1950), and the comonomer fraction was calculated as the fraction of ethylene in the polymer relative to all monomers in the polymer: fE=(E / (P+E). The comonomer fraction is given by 13 C{ 1The ethylene content was quantified using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) by integration of multiple signals over the entire spectral range of the {H} spectrum. This method was chosen for its robustness and ability to take into account the presence of positional defects when necessary. The integration region was slightly adjusted to increase applicability over the full range of comonomer contents encountered. For systems with very low ethylene content, where only isolated ethylene in the PPEPP sequence is observed, the method of Wang et al. was modified to reduce the impact of integration of sites that are no longer present. This approach reduces the overestimation of ethylene content for such systems, which was accomplished by reducing the number of sites used to determine the absolute ethylene content to E = 0.5 (Sββ + Sβγ + Sβδ + 0.5 (Sαβ + Sαγ)). With this set of sites, the corresponding integral equation can be written as E = 0.5(I H +I G +0.5(I C +I D )). The equation used for absolute propylene content was not modified. Comonomer incorporation in mole percent was calculated from the mole fraction: E[mol%]=100×fE. Comonomer incorporation in weight percent was calculated from the mole fraction: E[wt%]=100×(fE×28.06) / ((fE×28.06)+((1−fE)×42.08)).
[0083] i) Comonomer Content The content was determined by the film thickness method using the intensity I(q) of the quantitative band and the thickness T of the pressed film according to the following relationship: [I(q) / T]m+c=C, where m and c are 13 The coefficients were determined from a calibration curve constructed using the comonomer contents obtained from C-NMR spectroscopy. The comonomer content is 13The spectra were measured in a known manner based on Fourier transform infrared spectroscopy (FTIR) using a Nicolet Magna 550 IR spectrometer with Nicolet Omnic FTIR software, calibrated with C-NMR. Films with a thickness of about 250 μm were compression molded from the samples. Similar films were made from calibration samples with known comonomer contents. The comonomer contents were measured using a 1430-1100 cm -1 The absorbance was determined from the spectrum in the wavenumber range of 1410 to 1320 cm. The absorbance was measured as the height of the peak by choosing a so-called short baseline or a long baseline or both. The short baseline was measured from about 1410 to 1320 cm through the lowest point. -1 The long baseline is about 1410~1220cm -1 An individual calibration had to be performed for each baseline type, and the comonomer content of the unknown samples was within the range of the comonomer content of the calibration samples.
[0084] j) MFR The melt flow rate was measured at 230°C (polypropylene-based materials) or 190°C (polyethylene-based materials) under a load of 2.16 kg (MFR2). The melt flow rate is the amount of polymer in grams that an ISO 1133 standardized test apparatus extrudes under a load of 2.16 kg at a temperature of 230°C (or 190°C) within 10 minutes.
[0085] k)density Density was measured according to ISO 1183-187. Sample preparation was performed by compression molding according to ISO 1872-2:2007.
[0086] l) Heat deflection temperature (HDT) HDT was prepared according to ISO 1873-2 and stored at +23°C for at least 96 hours before measurement. 3 The strength was determined on injection moulded specimens of 0.45 MPa. Tests were performed on flat supported specimens according to ISO 75, condition B, with a nominal surface stress of 0.45 MPa.
[0087] m) Coefficient of linear thermal expansion (CLTE) The coefficient of linear thermal expansion (CLTE) was determined according to ISO 11359-2:1999 on 20 10 mm long pieces cut from the same injection-molded specimens used for the determination of the tensile modulus. Measurements were performed in the longitudinal (machine) direction in the temperature ranges -30 to +80 °C (or -30 to +85 °C) at a heating rate of 1 °C / min and 23 to +80 °C (or 23 to +85 °C) at a heating rate of 1 °C / min, respectively.
[0088] n) Tiger Stripes (MSE) or Flow Marks The tendency to show flow marks was investigated by the following method, which is described in detail in WO 2010 / 149529, which is incorporated herein in its entirety. An optical measurement system described by Sybille Frank et al. in PPS 25 Intern. Conf. Polym. Proc. Soc 2009 or Proceedings of the SPIE, Vol. 6831, pp. 68130T-68130T-8 (2008) was used to analyze the surface quality. This method has two aspects. 1. Recording images: The basic principle of this measurement system is to illuminate the plate with a defined light source (LED) in a closed environment and to record the image with a CCD camera system. 2. Image Analysis: The test piece is floodlit from one side (full illumination) and the upward reflected part of the light is refracted via two mirrors onto a CCD sensor. The grey value image thus produced is analysed row by row. From the deviation of the recorded grey values, the mean square error (MSE) is calculated, which allows the quantification of the surface quality: the higher the MSE value, the more pronounced the surface defects. In general, for one and the same material, the higher the injection speed, the higher the tendency towards flow marks. For this evaluation, a 440 x 148 x 2.8 mm film was used with VW K50 grain and a 1.4 mm film gate. 3Plates were used and these plates were manufactured with different filling times of 1.5 seconds, 3 seconds and 6 seconds respectively. Further conditions: Melting temperature: 240℃ Mold temperature: 30℃ Dynamic pressure: 10bar hydraulic pressure The smaller the MSE value at a particular filling time, the less tendency for flow marks.
[0089] experiment Catalyst system: For the polymerization process of HECO2, a Ziegler-Natta type catalyst was used as used in the inventive examples of WO 2016 / 066446 A1 and as described in detail therein. For the polymerization processes of HECO1 and HECO3, the same catalyst was used except that it was prepolymerized with vinylcyclohexane to nucleate poly(vinylcyclohexane). Nucleation by prepolymerization with vinylcyclohexane is described in detail in EP 2960256 B1 and EP 2960279 B1, which are incorporated by reference. In all cases, triethylaluminum (TEAL) was used as the cocatalyst and dicyclopentadienyl-dimethoxysilane (Donor D) was used as the external donor, with the respective feed ratios shown in Table 1 below.
[0090] HECO1, HECO2 and HECO3 were produced in a Borstar PP pilot plant with a prepolymerization / loop reactor / gas phase reactor 1 / gas phase reactor 2 / gas phase reactor 3 configuration followed by a pelletization process.
[0091] [Table 1(1)] [Table 1(2)]
[0092] The heterophasic copolymers HECO1, HECO2 and HECO3 were compounded at 220° C. in a co-rotating twin screw extruder Coperion ZSK 47 with 0.15 wt. % of an antioxidant (Irganox B215FF from BASF AG, Germany, which is a 1:2 mixture of pentaerythrityl-tetrakis(3-(3′,5′-di-tert-butyl-4-hydroxyphenyl)-propionate, CAS number 6683-19-8 and tris(2,4-di-t-butylphenyl)phosphite, CAS number 31570-04-4), 0.05 wt. % of Ca stearate (CAS number 1592-23-0, commercially available from Faci, Italy). CRYSTEX QC analysis of these three copolymers gave the results listed in Table 2.
[0093] [Table 2]
[0094] Table 3 shows the properties of the polypropylene / polyethylene blends (A) used in the evaluation. The properties are shown as ranges since these compositions originate from a mechanical recycling process.
[0095] [Table 3]
[0096] HDPE1 is 955kg / m 3 The commercial grade was MB5568 from Borealis AG, Austria, having a density of 0.2 g / 10 min (ISO 1183), a MFR2 (2.16 kg, 190° C., ISO 1133) of 0.8 g / 10 min and a tensile modulus (ISO 527-2) of 1000 MPa.
[0097] HDPE2 is 954kg / m 3The material used was a commercial grade MB7541 from Borealis AG, Austria, having a density of 1000 nm (ISO 1183), a MFR2 of 4 g / 10 min (2.16 kg, 190° C., ISO 1133) and a tensile modulus of 850 MPa (ISO 527-2).
[0098] Plastomer 1 is commercially available from DOW, Inc., USA, and has a viscosity of 857 kg / m 3 The copolymer was Engage 8842, an ethylene-1-octene plastomer with a density of 1.0 g / 10 min and a MFR2 (2.16 kg, 190° C., ISO 1133) of 1.0 g / 10 min.
[0099] Plastomer 2 is commercially available from DOW, Inc., USA, 863 kg / m 3 The polymer was Engage 8180, an ethylene-1-octene plastomer with a density of 0.01 g / 10 min and a MFR2 (2.16 kg, 190° C., ISO 1133) of 0.5 g / 10 min.
[0100] Talc 1 is commercially available from IMERYS, France, and has a diameter of 2.0 μm. 50 and d of 10.0 μm 95 The fluororesin was Luzenac HAR T84 with Sedigraph measurement.
[0101] Talc 2 is commercially available from IMERYS, France, 1.2 μm d 50 and d of 3.3 μm 95 The chromatogram was obtained using a Jetfine 3CA with Sedigraph measurement.
[0102] The final compositions were compounded using the above polymers and talc along with antioxidants, UV stabilizers, slip agents, nucleating agents, carbon black masterbatch, calcium stearate, antifog agents in a Coperion ZSK40 twin screw extruder at 220° C. The compositions of the examples performed are shown in Table 4.
[0103] [Table 4]
[0104] Table 5 shows the characteristics of the examples carried out.
[0105] [Table 5] * CLTE was evaluated from +23°C / 85°C. Data can be compared with data measured from +23 / 80°C. nm = not measured.
[0106] The compositions according to the invention are found to exhibit improved impact properties in instrumented impact tests even at low temperatures, and good surface appearance with low tiger stripes, and are therefore suitable for automotive interior molded articles, even though they contain up to 40% by weight of mixed plastic polypropylene blends derived from post-consumer waste.
Claims
1. A composition suitable for automotive applications obtained by blending at least components (A), (B) and (C), (A) 15% to 50% by weight of a mixed plastic polypropylene blend; (B) 10% to 60% by weight of a heterophasic propylene copolymer, and (C) 5% by weight to 25% by weight of an inorganic filler; All percentages are given relative to the total composition. The mixed plastic polypropylene blend (A) is Originating from post-consumer and / or industrial waste and containing polypropylene and polyethylene; A crystalline fraction (CF) content determined according to CRYSTEX analysis obtained by temperature cycling of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. ranging from 85.0 to 96.0% by weight; and Soluble fraction (SF) content determined according to CRYSTEX analysis obtained by temperature cycle of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. ranging from 4.0 to 15.0% by weight. having The crystalline fraction (CF) is in the range of 1.0 to 10.0% by weight. 13 having an ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; The soluble fraction (SF) has an intrinsic viscosity (iV(SF)) measured in decalin according to DIN ISO 1628 / 1 at 135° C. in the range of 0.9 to 2.1 dl / g, The heterophasic propylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein, detectable by high resolution microscopy; Melt flow rate (MFR) of 85 to 250 g / 10 min 2 (230℃, 2.16kg, ISO1133), a soluble fraction (SF) content determined according to CRYSTEX analysis obtained by temperature cycling of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. ranging from greater than 20.0% by weight to 30.0% by weight; and Intrinsic viscosity (iV(SF)) of the soluble portion, measured in decalin according to DIN ISO 1628 / 1 at 135° C., of 2.0 to 4.5 dl / g having The composition comprises: Melt flow rate (MFR) of 20 to 60 g / 10 min 2 (230℃, 2.16kg, ISO1133) A composition comprising:
2. It is obtained by blending components (A), (B), (C) and one or more of the following components: (D) 0 to 25 wt. % of a second heterophasic propylene copolymer; (E) 0 to 10% by weight of high density polyethylene; (F) 0 to 20% by weight of an ethylene-based plastomer; All percentages are given relative to the total composition. said second heterophasic propylene copolymer (D) comprises a matrix phase and an elastomeric phase dispersed therein, detectable by high resolution microscopy; Melt flow rate (MFR) of 8 to 25 g / 10 min 2 (230℃, 2.16kg, ISO1133), a soluble fraction (SF) content determined according to CRYSTEX analysis obtained by temperature cycling of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. ranging from 12.5 to 30.0% by weight; and The intrinsic viscosity iV (SF) of the soluble portion measured in decalin according to DIN ISO 1628 / 1 at 135° C. in the range of 2.3 dl / g to 6.0 dl / g having The high density polyethylene (E) is Melt flow rate (MFR) of 0.5 to 30.0 g / 10 min 2 (190°C, 2.16 kg, ISO1133), and 945-965kg / m 3 Density of having The ethylene-based plastomer, which is a copolymer of ethylene and a comonomer unit selected from an α-olefin having 3 to 12 carbon atoms, Melt flow rate (MFR) of 0.2 to 2.5 g / 10 min 2 (190°C, 2.16 kg, ISO1133), and 850-870kg / m 3 Density of The composition of claim 1 having the formula:
3. obtained by blending components (A), (B), (C) and (F), in the absence of (D) and (E); (A) 15% to 35% by weight of a mixed plastic polypropylene blend; (B) 30% to 60% by weight of a first heterophasic propylene copolymer; (C) 5% to 25% by weight of an inorganic filler, and (F) 5% to 20% by weight of an ethylene-based plastomer; All percentages are given of the total composition The composition of claim 2.
4. obtained by blending components (A), (B), (C), (E) and (F), in the absence of (D); (A) 25% to 50% by weight of a mixed plastic polypropylene blend; (B) 20% to 50% by weight of a first heterophasic propylene copolymer; (C) 5% by weight to 25% by weight of an inorganic filler; (E) 2% to 10% by weight of high density polyethylene, and (F) 2% to 20% by weight of an ethylene-based plastomer; All percentages are given of the total composition The composition of claim 2.
5. obtained by blending components (A), (B), (C), (D) and (E), in the absence of (F); (A) 25% to 50% by weight of a mixed plastic polypropylene blend; (B) 15% to 30% by weight of a first heterophasic propylene copolymer; (C) 5% by weight to 25% by weight of an inorganic filler; (D) 5% to 25% by weight of a second heterophasic propylene copolymer, and (E) 2% to 10% by weight of high density polyethylene; All percentages are given of the total composition The composition of claim 2.
6. The inorganic filler (C) is Median particle size before compounding d from 0.3 to 30.0 micrometers 50 and / or Top cut particle size before compounding d from 1.0 to 50.0 micrometers 95 The composition of claim 1 which is a talc having the formula:
7. A crystalline fraction (CF) content determined according to CRYSTEX analysis obtained by temperature cycling of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. ranging from 60.0 to 90.0% by weight; and Soluble fraction (SF) content determined according to CRYSTEX analysis obtained by temperature cycle of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C., ranging from 10.0 to 40.0% by weight. having The crystalline fraction (CF) is in the range of 4.0 to 15.0% by weight. 13 and / or having an ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; the crystalline fraction (CF) has an intrinsic viscosity (iV(CF)), measured in decalin according to DIN ISO 1628 / 1 at 135° C., of less than 1.8 dl / g; and / or The soluble fraction (SF) is in the range of 28.0 to 65.0% by weight. 13 having an ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; and The soluble fraction (SF) has an intrinsic viscosity (iV(SF)) measured in decalin according to DIN ISO 1628 / 1 at 135° C. of more than 1.7 dl / g. The composition of claim 1.
8. 2. The composition of claim 1 having a flexural modulus of from 1500 MPa to 2200 MPa.
9. 5.0 kJ / m 2 ~50.0 kJ / m 2 2. The composition of claim 1, having a Charpy notched impact strength at 23°C of
10. 2. The composition of claim 1, having a deflection temperature under load (ISO 75B) of at least 95° C. and / or a coefficient of linear thermal expansion (CLTE) of 60 to 125 μm / mK.
11. 2. The composition of claim 1, having a puncture energy of 12 to 65 J and / or a maximum impact force energy of 10 to 60 J, as determined in an instrumented drop weight test according to ISO 6603-2 at 23°C.
12. An article comprising the composition of any one of claims 1 to 11.
13. has an MSE surface quality of less than 15; The article of claim 12, wherein the MSE surface quality is measured for a plate-shaped specimen of 440 x 148 x 2.8 mm3 by recording images of the surface of the plate-shaped specimen with a CCD camera system and calculating the mean square error (MSE) from the deviation of the recorded grey values.
14. 12. Use of a composition according to any one of claims 1 to 11 for injection moulding of an article.
Citation Information
Patent Citations
Polypropylene composition
JP1983168649A
Multilayer plastic vessel
JP1994320689A
Polypropylene composition
JP1997208797A
Ultra-high molecular weight polyethylene-made porous sintered body
JP2016176061A
Polypropylene-polyethylene composition with improved flowability
JP2018532859A
